NUTRITIONAL CHARACTERISTICS AND DIETARY INTAKE OF PATIENTS ATTENDING THE PRE-DIALYSIS ASSESSMENT CLINIC - Maria Chan; John Kelly; Marijka Batterham; Linda Tapsell (The Korean Society of Nephrology, 2012)
Poor nutrition status at the start of dialysis is associated with morbidity and mortality. Timely management of patients with ESKD pre-dialysis including providing nutrition intervention is important. The aim of this study was to describe the baseline nutritional status and dietary intake of patients attending the pre-dialysis assessment clinic. Of the 210 patient assessed, 60.5% were male; mean age was 65.7±13.6 years and mean GFR was 17.0±4.2 ml/min. 17.1% were underweight (BMI<23 kg/m2) while 62.5% were overweight or obese (BMI>26 kg/m2). 39.5% were rated as malnourished (SGA score B&C) and 18.5% were overweight/obese and malnourished. 26.7% had MAMC 10% less than 50th percentile of the standard. Mean energy and protein intakes were 23.4±6.9 kcal/kg IBW/d and 1.16±0.43 g/kg IBW/d with 65.5% and 15.6% did not meet the recommended intake of energy and protein respectively. 48% of patients experienced symptoms (e.g. poor appetite and nausea) affecting dietary intake while 15.7% of patients self-imposed dietary restriction inappropriately due to misconception of nutrition requirements in ESKD. 41.4% and 85.2% did not consume adequate fruit and vegetables of 2 and 5 serves per day respectively based on the Australian Guide to Healthy Eating. Nutrient intake (prevalence %) below the Recommended Daily Intake (DRI) levels were: VitB1 (36.5%), VitB2 (43.5%), Niacin (3.9%), VitC (202%), VitE (41.0%), folate (83.2%), VitA (50.5%), Mg (94.5%), Fe (36.1%), Zn (70.8%) and dietary fibre (83.3%). In conclusion, patients attended the current pre-dialysis assessment clinic presented with parameters indicative of poor nutritional health. This clinic may provide an opportunity to optimise nutritional status of ESKD patients before dialysis is required.